2010
DOI: 10.1039/c0cc01345e
|View full text |Cite
|
Sign up to set email alerts
|

An alkynylboronate cycloaddition strategy to functionalised benzyne derivatives

Abstract: A new approach to benzyne precursors has been developed that involves the [4+2] cycloaddition of trimethylsilyl alkynylboronates with 2-pyrones, followed by oxidation and trifluoromethylsulfonylation of the boronate moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Thus, this cycloaddition methodology appears to be a convenient platform from which a range of new stereochemically defined 1,2-disubstituted BCBs can be obtained. Because of the easy access to various aryne precursors [4143] and the various functionalized BCBs that can be obtained from them, this chemistry is likely to see utility in wide-ranging areas, from organic synthesis to materials chemistry, and electronics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this cycloaddition methodology appears to be a convenient platform from which a range of new stereochemically defined 1,2-disubstituted BCBs can be obtained. Because of the easy access to various aryne precursors [4143] and the various functionalized BCBs that can be obtained from them, this chemistry is likely to see utility in wide-ranging areas, from organic synthesis to materials chemistry, and electronics.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the regiochemistry is believed to be mainly controlled by the steric bulkiness of the C3-silyl group of 4f. 68) Despite extensive examples in the literature involving the reactions of halobenzynes with a range of arynophiles, [79][80][81][82][83][84][85][86][87][88][89][90][91][92] the nucleophilic fluorination of halobenzynes 4h-4k, generated from 3h, 3i, 3j′, and 3k′, with Bu 4 NF(t-BuOH) 4 under normal batch conditions produced complex mixtures, and the yields of the expected fluorobenzenes 1 were very poor ( Table 3). In stark contrast, the reaction of 5-chloro-3-(tertbutyldimethylsilyl) benzyne (4h), generated from 3h, with Bu 4 NF(t-BuOH) 4 under the optimized flow conditions produced 1h in 51% yield as a mixture of two regioisomers (meta-1h/ortho-1h=1.2 : 1, Entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…It requires very little energy without catalyst, and thus has been widely used in many organic reactions [ 44 , 45 , 46 ]. Alkynylboronates have found to be reactive reagents to undergo the [2 + 4] cycloaddition to form six-membered functionalized organoboronates [ 47 , 48 ]. Harrity, et al ., found that alkynylboronates are relatively electron rich and thus have a cycloaddition reactivity that resembles that of acetylene.…”
Section: [2+4] Cycloadditionmentioning
confidence: 99%
“…Harrity, et al ., found that alkynylboronates are relatively electron rich and thus have a cycloaddition reactivity that resembles that of acetylene. Therefore, the [2 + 4] reactions between alkynylboronates and electron-rich dienes were unsuccessful [ 47 , 48 ]. The use of cyclopentadienones, tetrazines and 2-pyrones as diene components led to the formation of highly functionalized organoboron synthetic intermediates as outlined in Scheme 9 .…”
Section: [2+4] Cycloadditionmentioning
confidence: 99%